2019
DOI: 10.1177/0391398819885936
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes associated with sedation and analgesia in patients supported with venoarterial extracorporeal membrane oxygenation

Abstract: Sedatives and analgesics are frequently used in critically ill adult patients requiring mechanical ventilation in the intensive care unit, but optimal agent selection and dosing in patients supported with venoarterial extracorporeal membrane oxygenation remain poorly defined. This retrospective study evaluated whether sedative and analgesic agent selection and dosing had any impact on clinical outcomes after venoarterial extracorporeal membrane oxygenation decannulation. The primary endpoint of our study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…9,10 In addition, ECMO initiation and maintenance require adequate pain, agitation, and movement control to optimize ventilatory support and gas exchange in VV-ECMO, lower metabolic demand of VA-ECMO patients, and prevent potential harm. [11][12][13][14] Therefore, ECMO patients commonly receive higher doses of analgesic and sedative medications than patients with similar disease severity who are not receiving ECMO support. 15 Lack of evidence-based practice guidelines is more conspicuous during increased demand and medication shortage, as experienced in the ongoing COVID-19 pandemic.…”
mentioning
confidence: 99%
“…9,10 In addition, ECMO initiation and maintenance require adequate pain, agitation, and movement control to optimize ventilatory support and gas exchange in VV-ECMO, lower metabolic demand of VA-ECMO patients, and prevent potential harm. [11][12][13][14] Therefore, ECMO patients commonly receive higher doses of analgesic and sedative medications than patients with similar disease severity who are not receiving ECMO support. 15 Lack of evidence-based practice guidelines is more conspicuous during increased demand and medication shortage, as experienced in the ongoing COVID-19 pandemic.…”
mentioning
confidence: 99%
“…In a small, retrospective study of patients receiving ECMO, delirium was reported in 47% of patients where 60% of the entire cohort were exposed to benzodiazepines. 24 Interestingly, rates of delirium were not different in patients that had a 50% or more reduction in their benzodiazepine requirements within 48 h of ECMO decannulation. Since many of these studies were retrospective, single center, and used institution-specific guidelines for sedation and analgesia, future research surrounding chemical and physiologic parameters that influence opioid and sedative clearance and the resultant long-term clinical outcomes associated with different practices are necessary.…”
Section: Sedation and Analgesiamentioning
confidence: 93%
“…The long‐term impact of high doses of opioids and sedatives in patients receiving ECMO is largely unknown. In a small, retrospective study of patients receiving ECMO, delirium was reported in 47% of patients where 60% of the entire cohort were exposed to benzodiazepines 24 . Interestingly, rates of delirium were not different in patients that had a 50% or more reduction in their benzodiazepine requirements within 48 h of ECMO decannulation.…”
Section: Sedation and Analgesiamentioning
confidence: 95%